Uncertainty shocks, capital flows, and international risk spillovers - Ozge Akinci; Sebnem Kalemli-Ozcan; Albert Queralto (Federal Reserve Bank of New York, 2022)
Foreign investors' changing appetite for risk-taking has been shown to be a key determinant of the global financial cycle. Such fluctuations in risk sentiment also correlate with the dynamics of uncovered interest parity (UIP) premia, capital flows, and exchange rates. To understand how these risk sentiment changes transmit across borders, we propose a two-country macroeconomic framework. Our model features cross-border holdings of risky assets by U.S. financial intermediaries that operate under financial frictions and act as global intermediaries in that they take on foreign asset risk. In this setup, an exogenous increase in U.S.-specific uncertainty, modeled as higher volatility in U.S. assets, leads to higher risk premia in both countries. This occurs because higher uncertainty leads to deleveraging pressure on U.S. intermediaries, triggering higher global risk premia and lower global asset values. Moreover, when U.S. uncertainty rises, the exchange rate in the foreign country vis-a-vis the dollar depreciates, capital flows out of the foreign country, and the UIP premium increases in the foreign country and decreases in the U.S., as in the data.
Keywords: E32; E44; F41; 330; financial frictions; risk premia; time-varying uncertainty; intermediary asset pricing; financial spillovers; global financial cycle; Kapitalmobilität; Auslandsinvestition; Risikopräferenz; Risikokapital; Zinsparität; Risikoprämie; Spillover-Effekt; USA